Specific Association of HLA–DRB1*03 With Anti–Carbamylated Protein Antibodies in Patients With Rheumatoid Arthritis. Issue 3 (28th January 2019) - Regueiro, Cristina; Rodríguez‐Rodríguez, Luis; Triguero‐Martinez, Ana; Nuño, Laura; Castaño‐Nuñez, Angel L.; Villalva, Alejandro; Pérez‐Pampín, Eva; Lopez‐Golan, Yolanda; Abasolo, Lydia; Ortiz, Ana M.; Herranz, Eva; Pascual‐Salcedo, Dora; et al.
Abstract : Objective: Recognition of a new type of rheumatoid arthritis (RA)–specific autoantibody, the anti–carbamylated protein antibodies (anti‐CarP), has provided an opportunity to improve the management and understanding of RA. The current study was undertaken to assess the relationship between anti‐CarP antibodies and HLA–DRB1 alleles in RA. Methods: Serum samples were obtained from 3 different collections, comprising a total of 1, 126 RA patients. Serum reactivity against in vitro carbamylated fetal calf serum proteins was determined by enzyme‐linked immunosorbent assay. HLA–DRB1 alleles were determined using either hybridization techniques or imputation from HLA‐dense genotypes. Results of these analyses were combined in a meta‐analysis with data from 3 previously reported cohorts. The carrier frequencies of the common HLA–DRB1 alleles were compared between the antibody‐positive RA subgroups and the double‐negative subgroup of RA patients stratified by anti–citrullinated protein antibody (ACPA)/anti‐CarP antibody status, and also between the 4 RA patient strata and healthy controls. Results: Meta‐analysis was conducted with 3, 709 RA patients and 2, 305 healthy control subjects. Results revealed a significant increase in frequency of HLA–DRB1*03 carriers in the ACPA−/anti‐CarP+ subgroup as compared to ACPA−/anti‐CarP− RA patients and healthy controls; this was consistently found across the 6 sample collections. This association of HLA–DRB1*03 with ACPA−/anti‐CarP+ RA was independent of the presence of the shared allele ( SE ) and any other confounders analyzed. No other allele was specifically associated with the ACPA−/anti‐CarP+ RA patient subgroup. In contrast, frequency of the SE was significantly increased in the ACPA+/anti‐CarP− and ACPA+/anti‐CarP+ RA patient subgroups, without a significant distinction between them. Furthermore, some alleles (including HLA–DRB1*03 ) were associated with protection from ACPA+ RA. Conclusion: These findings indicate a specific association of HLA–DRB1*03 with ACPA−/anti‐CarP+ RA, suggesting that preferential presentation of carbamylated peptides could be a new mechanism underlying the contribution of HLA alleles to RA susceptibility.